Avaliação para o uso da bicicleta: estudo de caso do Campus I da UFPB e seu entorno imediato - Cevada, Caroline Muñoz (2015)
The main objective of this work is to evaluate the bicycle as an alternative to improving the urban mobility, taking as a case study the Campus I of UFPB. For the development of research, focused on three methodological steps: referential research, physical, environmental and urban mobility diagnosis, and user profile (current and potential) of the bicycle. Several methodological techniques in extensive field work, due to lack of data about the study object focusing on the bike were used. From the applied methodology, it was observed that in terms of physical infrastructure of the campus, the bicycle is not contemplated as a means of transport, presenting only few paraciclos by the territory and no other facilitation the displacement of the bicycle. Currently it was revealed that there is demand for cyclists across campus, and several respondents stated interest in change in other modes of transport for the use of bicycles. It is concluded that there are several possibilities of incentives and increase of demand for bikers on campus, mainly in the case of addition to the infrastructural system of urban mobility for the bike. In order to maximize the use of bicycles in the subject matter, it was proposed two moments of action for implementation of cycling infrastructure and a stock frame for improvements to bicycle use, described by short, medium and long term. It is considered that this dissertation collaborated to the indication points to consider for the urban planning of the campus in order to prioritize the bicycle as a means of transport.